Academic Supervision of Supervisor in Improving Teachers Pedagogic Competences at Melati Cluster in Banda Aceh - Muzzayin, Muzayyin; Murniati, Murniati; Niswanto, Niswanto (Jurnal Pendidikan Progresif, 2021)
The aim of this research is to obtain complete and accurate data of school about academic Supervision of Supervisor in Improving Teachers Pedagogic Competences at Melati Cluster in Banda Aceh. This study used descriptive method with a qualitative approach. The data collection technique was conducted by observation, interview, and documentation study. The instrument used in this research is interview guidelines. The subjects of this study were supervisors, principal, and teachers. The result of this study shows that (1) Supervision programs were settled relying on the evaluation of the previous year supervision. It was established individually at the beginning of the academic year. Academic supervision program that is teacher training in planning, implementing and assessing learning outcomes. (2) The supervision done by school supervisor has been effective relying on the technique and procedures. The technique applied is individual and group techniques (3) Academic supervision follow up by school supervisor has been efficient and effective where at the end of the supervision as reports were there for teachers to read. Supervisors hold forum events like workshop, so it will help in improving the pedagogic competence. Keywords: academic supervision, pedagogic competence, Banda Aceh. DOI: 10.23960/jpp.v11.i2.202123